Enhance VR: A Multisensory Approach to Cognitive Training and Monitoring - Brugada-Ramentol, Victòria; Bozorgzadeh, Amir; Jalali, Hossein (Frontiers in Digital Health, 2022)
Cognitive training systems aim to improve specific domains or global cognition by engaging users in cognitively demanding tasks. While screen-based applications can improve performance in the trained cognitive abilities, they are often criticized for their poor transferability to activities of daily living. These systems, however, exclude the user's body and motor skills, which invariably serves to restrict the user experience. Immersive Virtual Reality (IVR) systems, in contrast, present the user with body-related information, such as proprioceptive and visuomotor information, allowing for an immersive and embodied experience of the environment. This feature renders VR a very appealing tool for cognitive training and neurorehabilitation applications. We present Enhance VR, an IVR-based cognitive training and monitoring application that offers short daily cognitive workouts. The games are designed to train and monitor specific cognitive domains such as memory, task flexibility, information processing, orientation, attention, problem-solving, and motor control. The aim is to test whether cognitively demanding tasks, presented in an IVR setting, provide a naturalistic system to train and monitor cognitive capabilities.